2022
DOI: 10.1111/jam.15719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, pH and sodium chloride on antimicrobial activity of magnesium oxide nanoparticles against E. coli O157:H7

Abstract: Aim This study was done to determine the effects of temperature, pH and sodium chloride (NaCl) on antimicrobial activity of magnesium oxide (MgO) nanoparticles (NPs) against E. coli O157:H7. Methods and results Culture conditions were established by varying the pH (5.0, 7.2 and 9.0), NaCl concentration (0.5, 2.0, 3.5 and 5.0%, w/v), and incubation temperatures (4, 12, 22 and 37°C). At each condition, the antimicrobial activities of MgO‐NPs (0, 1, 2 and 4 mg/ml) against E. coli O157:H7 were measured. Four‐way a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…From the results presented in Table 2 and Figure 5 , it is apparent that superior antibacterial potential of CP-MgONPs increases with concentration. Similar results were recently reported by Yoon et al who established that increasing the dosage of formed MgONPs improved their antibacterial activity towards E. coli [ 70 ]. Das et al also demonstrated the dose-dependent effectiveness of MgONPs towards the different strains of pathogens [ 71 ].…”
Section: Resultssupporting
confidence: 90%
“…From the results presented in Table 2 and Figure 5 , it is apparent that superior antibacterial potential of CP-MgONPs increases with concentration. Similar results were recently reported by Yoon et al who established that increasing the dosage of formed MgONPs improved their antibacterial activity towards E. coli [ 70 ]. Das et al also demonstrated the dose-dependent effectiveness of MgONPs towards the different strains of pathogens [ 71 ].…”
Section: Resultssupporting
confidence: 90%